Exploring the neural correlates of self-related names in healthy subjects. Issue 51 (18th December 2020) - Li, Ran; Du, Jubao; Chen, Weiguan; Zhang, Ye; Song, Weiqun
Abstract: Objectives: This study aimed to clarify the neural correlates and underlying mechanisms of the subject's own name (SON) and the unique name derived from the SON (SDN). Methods: A name that was most familiar to the subject (SFN) was added as a self-related reference. We used 4 auditory stimuli—pure tone (1000 Hz), SON, SDN, and SFN—to evaluate the corresponding activated brain areas in 19 healthy subjects by using functional magnetic resonance imaging. Results: Our results demonstrated that pure tone activated the fewest brain regions. Although SFN was a very strong self-related stimulus, it failed to activate many midline structures. The brain regions activated by SON and SDN were very similar. SFN as a self-related stimulus was less self-related compared with SDN. What's more, the additionally activated fusiform gyrus and parahippocampal gyrus of SDN might revealed its processing path. Conclusions: SDN, which has created by us, is a new and self-related stimulus similar to SON. They might provide a useful reference for consciousness assessment with SON and SDN.